Impact of a game-based tool on student engagement in a foreign language course: a three-term analysis - Anane, Chiraz (Frontiers in Education, 2024)
This paper explores the effectiveness of the game-based student response system Kahoot! in an online course for French as a foreign language. It examines how this tool impacted student engagement, motivation, and learning outcomes over three academic terms. The study combined quantitative data from structured questionnaires with qualitative insights from open-ended questions, providing a holistic view of the students' perceptions. The research was aimed at understanding the sustained impact of Kahoot! on learning and identifying any trends or variations in the student responses over time. This paper contributes to the field by offering a detailed analysis of Kahoot! in foreign-language education, particularly in an online setting. Throughout the three academic terms, high enthusiasm for and engagement with Kahoot! were consistently observed. The majority of the students expressed strong agreement about the tool's positive impact on learning, with high mean scores and low standard deviations indicating a broad consensus. However, variations in competitive motivation and some technical challenges were noted. Overall, this study underscores the sustained effectiveness of Kahoot! in enhancing student engagement and learning in online courses for French as a foreign language.